Prevalence and risk factors of microalbuminuria in type 2 diabetes mellitus - Mohan, Mane Madan; Sekhar V, Chandra (International Journal of Advances in Medicine, 2017)
Background: Microalbuminuria, which arises very early in the disease and is one of the first markers for diabetic nephropathy, is an independent risk factor for cardiovascular disease. This study was conducted to estimate the prevalence and the risk factors of microalbuminuria in type 2 diabetes mellitus. Methods: 246 patients having type 2 diabetes mellitus were included in the study wherein age, sex, duration of the diabetes and body mass index were noted. Blood pressure was taken for all the patients for detection of hypertension and blood was collected after fasting for a minimum of 12 hour for fasting blood sugar, glycosylated hemoglobin (HbA1C), serum cholesterol, and serum triglyceride levels. Results: Out of the 246 patients, 185 (75.2 %) of the patients had normal levels of albumin while 61(24.8%) of them had microalbuminuria. Incidence of males was more common and the mean age in which diabetes was detected among the patients enrolled was in the early 40s. High systolic blood pressure with mean value 135, fasting blood sugar 172, cholesterol 181, HbA1C 8.7 was observed among the patients. The average duration of diabetes was found to be 9 years among the patients with microalbuminuria. Conclusions: There is a high prevalence of microalbuminuria among the patients with diabetes type 2 in our geographical area. Hypertension, duration of diabetes, fasting blood sugar, HbA1c were found to be the risk factors. Therefore, the early identification of patients at greatest risk, and the subsequent initiation of renal and cardiovascular protective treatments, are of the utmost importance.